2010
DOI: 10.1007/s00247-010-1923-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiology residents’ experience with intussusception reduction

Abstract: BackgroundResidents should be exposed to adequate procedural volume to act independently upon completion of training. Informal inquiry led us to question whether residents encounter enough intussusception reductions to become comfortable with the procedure.ObjectiveWe sought to determine radiology residents’ exposure to intussusception reductions, and whether their experiences vary by region or institution.Materials and methodsU.S. radiology residency program directors were asked to encourage their residents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A survey found that senior radiology residents on average reported participating in only 2 cases during their entire residency; 22% had been involved in no reductions, and 21% had been involved only once [5]. A more recent survey found that pediatric radiology fellows have more experience with reducing intussusception, with respondents reporting an average of 6.9 reductions [6].…”
Section: Introductionmentioning
confidence: 99%
“…A survey found that senior radiology residents on average reported participating in only 2 cases during their entire residency; 22% had been involved in no reductions, and 21% had been involved only once [5]. A more recent survey found that pediatric radiology fellows have more experience with reducing intussusception, with respondents reporting an average of 6.9 reductions [6].…”
Section: Introductionmentioning
confidence: 99%